A Situation Study of Disruptive Technology and Innovation of Thai Construction Industry - Sridaranon, Tawan; Baobuangoen, Jidapa; Pornsing, Choosak; Tonglim, Tongtang; Tharawetcharak, Pattrawet (Journal of Advanced Development in Engineering and Science, 2023)
This research aims to study the situation of modern technology and innovation disruption in Thai construction industries. The article started from conducting a specific field survey to a sample of 86 establishments of Thai construction industries registered as a member of Thai Contractors Association under H.M. The King's Patronage. The sample of research is calculated by using Taro Yamane formula, it was found that there was a 90 percent confidence level from 580 establishments. The result of the research showed that, 32.5% of large and medium enterprises have an adjustment of technology and innovation policy under Thai industrial revolution 4.0, and are ready to compete with foreign enterprises more efficiently than small and medium enterprises. In addition, a synthesis of guidelines for competitiveness of Thai construction industries, it is found that Thai construction industries should develop a cluster, and skilled workers to be expert in modern technology and innovation, such as Internet of Thing (IoT), Big Data Technology, and Building Information Modeling (BIM). In the form of sharing technology and innovation with participation in driving the Thai construction industry to be able to adapt according to the situation of technology and innovation disruption with potential.